Effect of NaOCl and EDTA irrigating solutions on the cyclic fatigue resistance of EdgeTaper Platinum instruments - Hussam Alfawaz; Abdullah Alqedairi; Maha Alhamdan; Najla Alkhzim; Shatha Alfarraj; Ahmed Jamleh (BMC, 2022)
Abstract Background To compare the solution on the cyclic fatigue resistance of EdgeTaper Platinum (ETP) instruments with that of ProTaper Gold (PTG) in the presence of ethylenediaminetetraacetic acid (EDTA) or sodium hypochlorite (NaOCl) irrigating solutions. Methods Sixty PTG and 60 ETP instruments with the same size (#25) and taper (8%) were tested under 17% EDTA, 5.25% NaOCl, or distilled water (n = 20 each). Cyclic fatigue was tested using artificial canals that were milled in stainless steel blocks using a laser micromachining technique. The canals had a curvature angle of 60 and a curvature radius of 5 mm. The center of maximum curvature was set at 5 mm from the instrument tip. The block of artificial canals was stabilized inside a container that was filled with one of the tested solutions. The temperature was fixed at 37 °C with a tolerance limit of 1 °C. The number of cycles to fracture (NCF) was calculated and the fractured surfaces were examined using a scanning electron microscope. All statistical analyses were performed using SPSS software Version 20 (IBM-SPSS Inc., Chicago, IL) at a confidence level of 95%. Results ETP showed higher NCF than PTG in any of the tested solutions (P < 0.05). Within each group, NaOCl drastically decreased the NCF compared to water and EDTA (P < 0.05) and changing the solution from distilled water to EDTA did not affect the fatigue resistance (P > 0.05). Conclusions ETP showed improved cyclic fatigue performance compared to PTG in all tested irrigating solutions. EDTA can be used in combination with NiTi instruments during canal instrumentation without compromising the cyclic fatigue resistance of PTG and ETP instruments. However, NaOCl drastically decreased the NCF.